Improved DC and RF performance of InAlAs/InGaAs InP based HEMTs using ultra-thin 15 nm ALD-Al2O3 surface passivation. (April 2018) - Asif, Muhammad; Chen, Chen; Peng, Ding; Xi, Wang; Zhi, Jin
Highlights: Surface passivation for better DC and RF performance in InP based HEMTs. Passivation method: Atomic layer deposition ALD-Al2 O3 . Layer thickness = 15 nm ultra-thin, device Lg  = 100 nm. Improvement in the DC performance after passivation (increase in IDS, MAX, gm, MAX ). Improvement in the RF performance after passivation (increase in fmax, MAX ). Abstract: Owing to the great influence of surface passivation on DC and RF performance of InP-based HEMTs, the DC and RF performance of InAlAs/InGaAs InP HEMTs were studied before and after passivation, using an ultra-thin 15 nm atomic layer deposition Al2 O3 layer. Increase in Cgs and Cgd was significantly limited by scaling the thickness of the Al2 O3 layer. For verification, an analytical small-signal equivalent circuit model was developed. A significant increase in maximum transconductance ( gm ) up to 1150 mS/mm, drain current ( IDS ) up to 820 mA/mm and fmax up to 369.7 GHz was observed, after passivation. Good agreement was obtained between the measured and the simulated results. This shows that the RF performance of InP-based HEMTs can be improved by using an ultra-thin ALD-Al2 O3 surface passivation.